Post reform development in Asia - "Sanyal, Manoj Kumar. (ed.)" (Hyderabad, 2009)
This festschrift volume for Professor Amiya Kumar Bagchi dwells on issues often raised in the development debate whether neo-liberal reforms in developing nations have raised inequality and poverty, food insecurity, hindered empowerment of women, aggravated agrarian distress, reallocated resources for private profitability and facilitated the rise of multi-national oligopoly according inferior status to the domestic industries in the host countries. Most of the issues have been examined on the basis of empirical data drawn from China, India and Bangladesh. Essays on China concentrate on post-reform issues of inequality across regions and rural-urban locations and its failure to achieve targets of human development while experiencing rapid economic growth. Discussions on changes in policy environment since the early days of the People$1 (Bs Republic of China also constitute the basic themes of the essays. Food insecurity, growth-poverty-employment relationship, gender discrimination in the labour market and agrarian distress caused by withdrawal of state support to small farmers growing commercial crops and revision of priority sector lending policy at the cost of small farmers and entrepreneurs are the major themes of essays written in the Indian context of post-reform development. In an essay on Bangladesh the poverty issues has been revisited in the context of child work. Agrarian issues have also been raised in an essay where the author proposes an alternative peasant social construction for the dual affirmation of land rights of the state and of the peasant family. In the last two essays authors look far beyond the mainstream tradition to develop an analytical framework for understanding issues relating to the recent rise of multi-national firms and the phenomenal growth of India$1 (Bs software technology.s
Keywords: "Bagchi, Amiya Kumar-Festschrift volume"